LONG-TERM EFFECT OF OCCUPATIONAL DUST EXPOSURE - BAUER, Peter; WESTPHAL, Gerhard; NEUBERGER, Manfred (Sangyo Igaku, 1988)
In 1950-1960, a cohort of dust-exposed workers and a cohort of multiple matched unexposed subjects was set up from the files of preventive medical checkups performed in 1, 089 Viennese plants. Male workers with a history of long-term exposure to nonfibrous particulates in different industries (metal, ceramics, brick, glass, stone etc.) aged ≥40, and male workers without dust exposure (matched for residency, start of observation, age, and smoking) were followed up to 1980 or death (48, 960 person yr). By life table methods, dust-exposed workers compared to unexposed workers showed a reduced survival of age 60 (p<0.0001), due to lung cancer (123 exposed, 87 controls, p=0.001), stomach cancer (48/27, p=0.003), silicosis (40/0), emphysema, bronchitis and asthma (41/23, p=0.007). No difference in mortality from cardiovascular diseases was observed (p>0.50). We concluded that heavy and long term exposure to respirable particulates is related to increased lung cancer mortality after age 60. A comparison of 2, 212 deaths among Austrian silicotics, with deaths in the corresponding population showed a relation between lung cancer and silicosis (p<0.001), fairly independent of age and time-period. The estimated relative lung cancer risk of Austrian silicotics in the period 1955-79 averaged 1.41 (95% confidence 1.21-1.64).